Evaluating the health-related quality of life in Egyptian cardiac patients using the brief version of the World Health Organization Quality-of-Life Scale (WHOQOL-BREF): observational cross-sectional study - Elbarbary, Mohammed Ahmed; Heba Safwat Mousa; Walid Roshdy; Amr Alkassas (Heart Science Journal, 2025)
Background: Health-Related Quality of Life (HR-QoL) reflects how a disease and its treatment may affect a person and serves as an important measure for assessing outcomes. This study aims to evaluate HR-QoL among Egyptian cardiac patients. Methods: This observational cross-sectional study enrolled 400 participants, divided into group I for cardiac patients and group II for non-cardiac participants (control group). The HR-QoL was measured by applying the brief version of the World Health Organization quality of life questionnaire (WHOQOL-BREF). Results: Compared to the control group, the physical and psychological domain scores for the cardiac patients were significantly lower (54.73 ± 21.59 vs. 63.89 ± 16.87, p = <0.001) and (41.72 ± 14.49 vs. 44.72 ± 12.69, p = <0.028), respectively. No statistically significant difference was found in the social and environmental domains. Elderly, women, unmarried, and low-educated individuals had poorer scores. Ischaemic heart disease patients treated with percutaneous coronary intervention (PCI) had better overall health scores. Additionally, patients with ejection fraction (EF) between 31-40% showed the lowest scores in physical and psychological domains. The scores in all QoL domains were reduced in cardiac patients with superadded concurrent chronic diseases. Conclusions: The WHOQOL-BREF scale is a crucial tool for assessing the quality of life (QoL) of cardiac patients, particularly in physical and psychological health. It is essential to conduct national and regional assessments, even in each country, to improve medical services and quality of life among cardiac patients.